Taxonomy and natural history of the myrmecophilous genus Clinterocera Motschulsky, 1858 (Coleoptera: Scarabaeidae: Cetoniinae) from China and adjacent regions: revision of the C. jucunda species group - Xu, Hao; Qiu, Jian-Yue; Huang, Guo-Hua (Zootaxa, 2018)
The Clinterocera jucunda species group of the genus Clinterocera Motschulsky, 1858 is revised. Fourteen species are recognized within this group, including five new species described herein: C. brevifasciata Xu & Qiu, new species from northern Vietnam and China; C. krikkeni Xu & Qiu, new species from southwestern China; C. sinensis Xu & Qiu, new species from southern China; C. velutina Xu & Qiu, new species from Hainan, China; and C. vietnamensis Xu & Qiu, new species from central Vietnam and Laos. Clinterocera nigra (Kano, 1931) is elevated to the species level. Clinterocera donckieri (Bourgoin, 1924) revised status is revalidated from the synonymy with C. davidis (Fairmaire, 1878). Two new synonyms are proposed based on examination of types and additional specimens: C. humeralis (Moser, 1902) new synonym and C. cervenkai Krajčík, 2012 new synonym are placed as junior synonyms of C. jucunda (Westwood, 1873) and C. donckieri, respectively. Lectotypes are designated for C. davidis and C. humeralis. Diagnoses and colored illustrations of most species are provided, including other four rare species, C. bicolor (Nonfried, 1893), C. ishikawai (Kurosawa, 1973), C. raui (Paulian, 1961), and C. yunnana (Moser, 1911). A key and a detailed description for the species group are presented. Male genitalia, intraspecific variations, new distribution records, and natural history are given for most species. The relationship between Clinterocera and ants is discussed.